Accountability and integrity as unique column of good governance - Noluthando Matsiliza; Nyaniso Zonke (Public and Municipal Finance, 2017)
The authors contend that accountability and integrity in public affairs are best preserved through enhancement of an integral system of legal prescripts, law, institutional policies and protocols. In the post-apartheid, South African public officials and political office bearers have been continuously criticized for allegedly transgressing ethical codes. Democracy has been tested due to violations of accountability, integrity and misconducts in the South African public service. However, this study argues that integrity can be enhanced when the society and those that are governing can preserve through specialized institutions legislation where law-makers are working with civil society to instill the culture of integrity.It is imperative to balance what is required for public officials’ conduct and what is done through parliamentary controls and certain caveats of highest honor. The value of accountability and integrity in public affairs can enjoy a resurgence in the last and present decade as the arrangements for public officials to operate in an environment that promotes good governance. This study reveals some concerns over the lack of commitment to preserve existing structures that could serve as mechanisms to promote good governance. A qualitative document analysis is employed to draw data from literature review. This paper’s findings contribute towards ethics and good governance in public administration.